CHROME PLATING TO INCREASE THE ADDED VALUE OF HOME INDUSTRY METAL PRODUCTS IN WEST SUMATERA - Asfarizal Saad; Nurzal Nurzal; Aswir Premadi (LP2M - Institut Teknologi Padang, 2013)
Electroplating by using direct current (DC) electrical energy can be obtained with a rectifier or battery. The using of electric chrome plating forms hard surfaces, high aesthetic value, corrosion resistant, wear resistant, and much in demand by the public. In West Sumatra, most of home industry products of metal creation (steel, copper, brass) are not plated yet with chrome, so that, they become less attractive. Adding the electric chrome plating to the metal products is then expected to increase the value of those products. It is essential to electroplating copper (Cu) and nickel (Ni) first before chrome (Cr). It is to improve the adesivitas and brighten the metal. The system solution used are copper sulfate (CuSO4) i = 6.68 A/dm2, t = 2 min; nickel sulfate (NiSO4) i = 3.5 A/dm2, t= 2 min; and chrome acid (CrO3) i= 5.1 A/dm2, t= 20 min. Energy source is a 12 volt battery 60 amperes. The result showed that: a) Throwing Power solution tends to decrease after the first and second plating; b) the average of layer thickness Cu: 8.54 µm, Ni: 6.65 µm, and Cr: 3.23 µm; c) good adesivitas in which there’s no cracks even in 90oand 180obending.